The metabolic fate of ivermectin in host (Ovis aries) and parasite (Haemonchus contortus) - Vokřál, Ivan; Jedličková, Veronika; Jirásko, Robert; Stuchlíková, Lucie; Bártíková, Hana; Skálová, Lenka; Lamka, Jiří; Holčapek, Michal; Szotáková, Barbora (Parasitology, 2013)
Ivermectin (IVE), one of the most important anthelmintics, is often used in the treatment of haemonchosis in ruminants. The objective of our work was (1) to find and identify phase I and II metabolites of IVE formed by the Barber's pole worm (Haemonchus contortus), and (2) to compare IVE metabolites in helminths with IVE biotransformation in sheep (Ovis aries) as host species. Ultrahigh-performance liquid chromatography/tandem mass spectrometry (UHPLC/MS/MS) was used for this purpose. During in vitro incubations, microsomes (from adult worms or from ovine liver) and a primary culture of ovine hepatocytes were incubated with IVE. In the ex vivo study, living H. contortus adults were incubated in the presence of 1 μM IVE for 24 h. The results showed that the H. contortus enzymatic system is not able to metabolize IVE. On the other hand, 7 different phase I as well as 9 phase II IVE metabolites were detected in ovine samples using UHPLC/MS/MS analyses. Most of these metabolites have not been described before. Haemonchus contortus is not able to deactivate IVE through biotransformation; therefore, biotransformation does not contribute to the development of IVE-resistance in the Barber's pole worm.
Keywords: hepatocyty; Haemonchus; Animals; Anthelmintics; Microsomes; mikrozomy; ovce domácí; ovce; Chromatography, Liquid; kultivované buňky; hmotnostní spektrometrie; Hepatocytes; ivermektin; hemonchóza; Cells, Cultured; nemoci ovcí; Sheep; anthelmintika; Mass Spectrometry; zvířata; Sheep, Domestic; Haemonchiasis; chromatografie kapalinová; Sheep Diseases; Ivermectin